Food outlet visits, physical activity and body weight: variations by gender and race–ethnicity. Issue 2 (28th November 2008) - Frank, L; Kerr, J; Saelens, B; Sallis, J; Glanz, K; Chapman, J
Abstract : Purpose: Recent evidence documents significant associations between community design, physical activity and obesity when adjusting for demographic covariates. Yet it is well understood that energy imbalance and weight gain are also a function of dietary patterns, and perhaps the degree of access to healthy food choices. Methods: The current study builds upon the Atlanta-based SMARTRAQ study of over 10 000 respondents and reports an integrated assessment of obesity impacts of physical activity and food outlet visitation. Respondents in the SMARTRAQ survey aged 25–65 provided BMI, self-reported physical activity levels (IPAQ), demographic factors, and where they went for food over a 2 day period. Results: The relative effect of physical activity, neighbourhood walkability, and food outlet visitation on BMI differed significantly across gender and ethnicity. BMI in females increased with fast food and decreased with grocery store visitation and physical activity, but not with walkability or walking. BMI in males was not related to where they went for food but decreased with walking and overall physical activity and with walkability. Fast food visitation was associated with increased BMI in white respondents and grocery store visitation with decreased BMI in black respondents. Meeting moderate activity guidelines was associated with lower BMI in both black and white respondents, yet walking was only significant in predicting reduced BMI in white respondents. Conclusion: Obesity influences of physical activity, walkability, and where people go for food differ significantly across gender and ethnicity and offer important policy implications and insights for future research.